Numerical simulation of combustion, flow, and heat transfer process of an oilfield heating furnace under different production conditions. Issue 3 (7th January 2022) - Zhao, Xuefeng; Meng, Lan; Ma, Jianguo; Wang, Ronghuan; Tian, Chunyu; Lian, Hongjun; Gao, Xiaomeng; Wu, Gang
Abstract: Heating furnace is an important energy‐consuming equipment in oilfield. In order to evaluate the operation status of heating furnace more accurately, in this paper, the production process of heating furnace in an oilfield is studied by numerical simulation technology, and the specific reasons affecting its thermal efficiency are deeply explored. First, the numerical simulation model of oilfield heating furnace production process is established, which is to digitize the geometric structure of the heating furnace, study the characteristics of the geometric shape, and generate the appropriate calculation grid. Second, numerical simulation and analysis are carried out for the working process of the heating furnace under rated and nonrated conditions, respectively. The medium flow characteristics, flame shape, temperature distribution, and pipe temperature distribution in the heating furnace under different conditions are systematically discussed. Finally, through the simulation analysis, it is found that the burner rotating device is beneficial to strengthen the heat transfer, and the change of load will affect the efficiency of the heating furnace. Under the rated working condition, design exhaust temperature is 260℃, numerical result is 225.8℃, and the error is −13.2%; design export temperature of water is 60℃, numerical result is 58.1℃, and the error is −3.2%; design temperature difference between inlet and outlet of water is 30℃, numerical result is 28.1℃, and the error is −6.3%. The working process of oilfield heating furnace is a complex coupling heat transfer process of combustion, flow, and heat transfer. The numerical results show that the working process of oilfield heating furnace could be successfully realized by means of numerical simulation. Under variable load conditions, in order to ensure that the export temperature of water is close to design temperature, it is necessary to change the fuel quantity in equal proportion to the water quantity. It is hoped that the reported results provide interesting information among the oilfield heating furnace operators. Abstract : First, the numerical simulation model of oilfield heating furnace production process is established, which is to digitize the geometric structure of the heating furnace, study the characteristics of the geometric shape, and generate the appropriate calculation grid. Second, numerical simulation and analysis are carried out for the working process of the heating furnace under rated and nonrated conditions, respectively. The medium flow characteristics, flame shape, temperature distribution, and pipe temperature distribution in the heating furnace under different conditions are systematically discussed.